HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT DENGAN TIGA PILAR STBM DI WILAYAH KERJA PUSKESMAS BATUSUYA KABUPATEN DONGGALA - Mahyudin Syam, Dedi (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
The Indonesian government has actually carried out various Community-Based Total Sanitation (STBM) efforts, also known as Community Led Total Sanitation (CLTS), which is a government program in order to strengthen efforts to promote clean and healthy living, prevent the spread of environment-based diseases, improve community capacity, as well as implementing the government's commitment to increase access to drinking water and sustainable basic sanitation. The aim of the research was to determine the relationship between knowledge and attitudes of the community and the three pillars of STBM in the working area of the Batusuya Health Center, Donggala Regency. This type of research is analytic research with a cross sectional approach. This research was conducted on 12 May -10 June 2019. The population in the study totaled 12,118 people. Determining the sample size, taken using the Lameshow formula of 93 heads of households. Sampling for each hamlet was carried out by proportional random sampling. Bivariate analysis was used to determine knowledge, attitudes and actions by controlling using the chi square test. The results showed that public knowledge of open defecation had a p value = 0.001, community knowledge had CTPS with a p value = 0.000 and public knowledge had a p value = 0.000. Attitudes with open defecation with p value = 0.000, attitudes with CTPS with p value = 0.001 and attitudes with waste handling with p value = 0.000. The knowledge and attitudes of the people in the working area of the Batusuya Health Center are related to the habit of open defecation, hand washing with soap (CTPS) and waste management.